Decoupling Re-Analysis of CO2 Emissions and Economic Growth From Two Dimensions - Han, Yuling; Liu, Yiping; Liu, Xiao (Frontiers in Energy Research, 2022)
The conference of the parties (COP) 21 was a significant attempt by governments to make and monitor commitments to limit global warming. However, COP 23 “sought to continue the global momentum to decouple output from greenhouse gas (GHG) emissions”. Among the GHG, carbon dioxide (CO2) is the major one most countries worry about. This paper examined the decoupling situations of China’s CO2 emissions and economic growth, considering the country's progress situation from the year 2000 to 2019. For this, we employed two models: the Environment Kuznets Curve (EKC) model for exploring the long-run decoupling status and the influence factors on CO2 emissions and the Tapio model for the short-run decoupling status. Later, the Tapio model was extended to analyze the influence of industrial structure, energy structure and population structure. The long term results suggest that China’s CO2 emissions have not decoupled yet, but the emissions intensity has decoupled in mid-2006. The short decoupling results revealed that the degree of decoupling changed to weak from strong in the last five years. According to the influencing structure's results, the industrial and energy structure inhibited CO2 emissions, but their influence was not strong enough to offset the impact of economic growth; however, the population structure indorsed CO2 emissions. Lastly, we found an unusual verdict that the change of EKC curve into a U-shape from an inverted U-shape and the observed reason is the control variable introduction. We also observed that the turning point became greater after introducing the industrial structure separately. Overall, from the perspective of the observed decoupling trends, it is suggested that China should strengthen and further optimize its energy structure to match the industrial structure.